Effects of UHMWPE viscoelasticity on the squeeze‐film lubrication of hip replacements. Issue 2 (25th May 2021) - Lu, Xianjiu; Meng, Qingen; Jin, Zhongmin
Abstract: Many studies have been performed to analyse the lubrication of artificial joints since the pioneer work by the late Professor Duncan Dowson. However, the viscoelastic deformation of one of the most widely used bearing materials, ultra‐high‐molecular‐weight polyethylene (UHMWPE), has only been considered recently. The described study attempted to investigate the effect of UHMWPE viscoelasticity on the elastohydrodynamic lubrication of such a soft artificial hip replacement under squeeze‐film motion. A transient viscoelastic squeeze‐film lubrication model of a typical hip implant was developed and solved to obtain the film thickness and pressure distributions. A boundary film thickness was adopted to consider the direct and indirect lubricant contact conditions. The results showed that the viscoelasticity had marked effects on the squeeze‐film lubrication performance of UHMWPE artificial hip joints. The minimum film thickness in the viscoelastic model was smaller than that of the elastic model, causing an earlier direct contact. However, the film thickness within the central contact region in the viscoelastic model was greater than that of the elastic model due to the restricted flow of the lubricant, therefore enhancing the lubricating effect and particularly with a short relaxation time and mechanical loss factor.